Performance optimization of sorption-enhanced DME synthesis (SEDMES) from captured CO2 and renewable hydrogen - Tyraskis, I.; Capa, A.; Skorikova, G.; Sluijter, S. N.; Boon, J. (Frontiers in Chemical Engineering, 2025)
Sorption-enhanced dimethyl ether synthesis (SEDMES) is a powerful technology to produce dimethyl ether (DME) from captured CO2 and renewable H2. In situ water by-product removal by zeolites shifts the thermodynamic equilibrium of the reaction towards product formation. Sorption enhancement proved to provide a single-pass CO2 conversion above 90%. This work presents a modelling study of the SEDMES process to optimize its performance under varying conditions. A universal cycle was designed to fulfil the requirement of continuous DME production as well as feed and purge flows. The cycle design is based on a state-of-the-art pilot plant commissioned by TNO in 2023, located in Petten, The Netherlands. Multiple Pareto fronts were generated to express the trade-offs between DME productivity and carbon selectivity in the SEDMES process for the first time. The impact of such process parameters as operating pressure, cycle duration, amount of inert gases, tube geometry and feed flow rate was analysed. A general trend of increased carbon selectivity and productivity at higher pressure was observed and analyzed under relevant cycle durations. However, this enhanced performance comes with the negative side effect of higher DME loss associated at elevated pressure operation. The SEDMES process proved to be tolerant to high concentrations of inert gases such as N2, reducing the need for extensive pretreatment steps. A lower feed flow rate was found to positively impact carbon selectivity to DME, which is promising for operation under intermittent conditions. Finally, even a minor increase in tube diameter reduced the Gas Hourly Space Velocity (GHSV), enhancing DME selectivity in a manner comparable to the effect of lower feed flow rates. Maximum productivity increases from 2.2 kg/h with 50.2% DME selectivity at 20 bar to 3.6 kg/h with 88.5% DME selectivity at 50 bar. The optimal cycle duration for these points also increased from 113 to 233 min, respectively.